The Trump's Aggression Towards ICC and it's impact on Palestine Isreal Conflict - khan, Muhammad Nafees Khan (Dialogue Social Science Review (DSSR), 2025)
On November 21, 2024, the International Criminal Court (ICC) issued arrest warrants for Israeli Prime Minister Benjamin Netanyahu, former Defense Minister Yoav Gallant, and Hamas leader Mohammed Deif for alleged war crimes in the Israel-Palestine conflict, which has claimed over 40,000 civilian lives. On February 6, 2025, U.S. President Donald Trump, supporting ally Israel, imposed sanctions on ICC officials, freezing their U.S. assets and banning their entry. The U.S. is not an ICC member. These sanctions, criticized by 79 countries including the UK, France, and Canada, hinder the ICC’s ability to probe war crimes, particularly in Palestine. This could delay justice and embolden further Israeli military actions, possibly advancing the “Greater Israel” vision, worsening regional unrest. The sanctions undermine the ICC’s independence, threatening global justice and human rights principles. Trump’s lack of empathy for Palestinian victims has raised concerns about U.S. priorities. Experts urge the EU, UN, and others to support the ICC with funding and diplomacy. Without action, these sanctions may undo decades of progress in international justice, leaving vulnerable groups without accountability and fueling violence in the Middle East